DECISION MODEL FOR SUBSIDY HOME PURCHASE THROUGH FACILITIES MODERATED BY CORPORATE IMAGE (STUDY ON SUBSIDIZED HOUSE CONSUMERS IN JAMBI CITY) - Anggia Agustini Saputri; Syahmardi Yacob; Tona Aurora Lubis; Hanan Laras Sabrina (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This study aims to identify and analyze facilities in improving purchasing decisions with the corporate image as a moderating variable for consumers of subsidized housing in Jambi City. This study has a sample of 140 consumers using a purposive sampling method. The data measurement scale used in this study is the ordinal scale. The data analysis used is quantitative data analysis with data analysis tools using SMART PLS 3.0. This study provides the following conclusions: Facilities have a direct influence on purchasing decisions. Those good facilities will increase consumers to make purchasing decisions. Likewise, an increase in the corporate image can increase purchasing decisions. Vitra company as a moderation is able to increase the effect of facilities on purchasing decisions for consumers of subsidized housing in Jambi City